Assessing the psychological preparedness of Emergency Response Team (ERT) at Mobile Switching Centres (MSC) for Digi Telecommunications Sdn.Bhd. - Ng, Goot Seong (2001)
This study was conducted to assess the psychological skill of Emergency Response Teams (ERT) at various Mobile Switch Centers (MSC) for DiGi Telecom nationwide in responding to emergency at the work place. The research methodology adopted is by population and random sampling. The use of questionnaires based on the self assessment of psychological skills by Dr. Michael 1. Asken (1993) was used to study the strength and weaknesses on the performance or response of relevant psychological skills. The results on the effectiveness of the psychological skills for DiGi ERT were used as a comparison with the Bomba Hazmat Team Penang as control. The psychological skills profile consisting seven conditions namely: confidence, physical arousal, attention control, arousal control, imagery use, commitment, self talk use, and physical condition were examined and analyzed. The results show level of psychological preparedness of ERT and level of psychological varies among the MSC ERTs with a significance value of less than 0.05. The other demographic aspects regarding age, education, rank, duration in ERT, fire fighting experience and fire fighting training attended do have significant effects on psychological skills.